Potential effects of using biodiesel in road-traffic on air quality over the Porto urban area, Portugal. (January 2016) - Ribeiro, Isabel; Monteiro, Alexandra; Lopes, Myriam
Abstract: This work aims to assess the impacts of biodiesel blends use in road-traffic on air quality. In this frame, the air quality numerical modelling system WRF-EURAD was applied over Portugal and the Porto urban area, forced by two emission scenarios (including CO, NOx, PM10, PM2.5, NMVOC, formaldehyde, acetaldehyde, acrolein and benzene): a reference scenario, without biofuels, and a scenario where a B20 fuel (20% biodiesel/80% diesel, v/v) is used by the diesel vehicle fleet. Regarding carbonyl compounds, emission scenarios pointed out that B20 fuel can promote an increase of 20% on formaldehyde, acetaldehyde and acrolein emissions, leading to increments on equivalent ozone production. On the other hand, through the air quality modelling exercise, it was verified that the use of B20 helps in controlling air pollution, improving CO and NO2 concentrations in urban airshed in about 20% and 10%, respectively, taking into account a regional simulation grid. However, according to the urban scale simulation, NO2 levels can increase in about 1%, due to the use of B20, over the Porto urban area. For the remaining studied pollutants, namely PM10 and PM2.5, mean concentrations will be reduced all over the territory, however in a negligible amount of <1%. Highlights: A numerical modeling tool was used to explore the B20 usage impacts on air quality. Two case studies were selected: mainland Portugal and the Porto urban area. The use of B20 promotes slightly variation on emission patterns and on air quality.